EVALUATION OF SURGICAL OUTCOMES OF OSTEOPOROTIC VERTEBRAL COMPRESSION FRACTURE PATIENTS TREATED BY KYPHOPLASTY, AT MILITARY HOSPITAL 105 - Nguyen Thanh Bac,; Dao Van Thuy, (Tạp chí Y học Quân sự, 2024)
Purpose: To evaluate the surgical outcomes of osteoporotic vertebral fracture patients treated by kyphoplasty at Military Hospital 105. Subjects and Methods: A descriptive, retrospective study of 34 osteoporotic fractures patients who were treated by kyphoplasty at Military Hospital 105 from January 2021 to December 2021. Results: Immediately post operation, 100% of patients had significant pain relief compared to preoperation (average VAS score after surgery 1.91 ± 1.22); 100% of patients had vertebral body height restored (with moderate level 36.4%, good level 39.4%); The kyphosis corrected spine has statistical significance compared to before treatment (with p < 0.05).